2013
DOI: 10.3340/jkns.2013.53.4.228
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Recurrence Rate after Treatment for Primary Spinal Sarcomas

Abstract: ObjectiveWe have limited understanding on the presentation and survival of primary spinal sarcomas. The survival, recurrence rate, and related prognostic factors were investigated after treatment for primary sarcomas of the spine.MethodsRetrospective analysis of medical records and radiological data was done for 29 patients in whom treatment was performed due to primary sarcoma of the spine from 2000 to 2010. As for treatment method, non-radical operation, radiation therapy, and chemotherapy were simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
4
0
2
Order By: Relevance
“…For primary tumors such as Ewing sarcoma and osteosarcoma, surgery has been combined with RT in 15 reported cases. Because primary spinal tumors are very rare and their histological type, Tomita type and susceptibility to RT vary considerably, there is no standard recommendation for using RT that is applicable to all types of primary spinal tumor. One systematic review identified several articles focusing on Ewing sarcoma; these articles recommended RT after TES .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For primary tumors such as Ewing sarcoma and osteosarcoma, surgery has been combined with RT in 15 reported cases. Because primary spinal tumors are very rare and their histological type, Tomita type and susceptibility to RT vary considerably, there is no standard recommendation for using RT that is applicable to all types of primary spinal tumor. One systematic review identified several articles focusing on Ewing sarcoma; these articles recommended RT after TES .…”
Section: Methodsmentioning
confidence: 99%
“…Cho and Chang reported that the outcomes of PVP combined with multi-needle interstitial implantation of 125 I seeds in patients with osteolytic metastatic vertebral tumors appeared to be better than those of PVP combined with single-needle interstitial implantation of 125 I seeds. These superior outcomes may be the result of the greater volume of bone cement injected and the better spatial distribution of the 125 I seeds with the multi-needle treatment 68 . Zhang et al also reported combining implantation with PVP and confirmed the above conclusions 90 .…”
Section: Intraoperative Radiotherapy and Brachytherapymentioning
confidence: 99%
“…В их структуре преобладают остеосаркома, саркома Юинга и хондросаркома. Хондросаркома составляет от 7 до 12 % всех ЗНО позвоночника, остеосаркомаот 3 до 14 %, саркома Юинга -от 5 до 8 % [8].…”
Section: обзор литературыunclassified
“…As with other common malignancies, distant metastasis (DM) was also reported to be a significant factor affecting the survival rate of patients with POSNs ( 8 ), and the occurrence of metastatic disease would greatly decrease the survival time of these patients ( 9 , 10 ). More frustratingly, these metastases usually remain asymptomatic until they progress to the point of destroying the organ function and are therefore easily overlooked.…”
Section: Introductionmentioning
confidence: 99%